2008
DOI: 10.1042/bj20070665
|View full text |Cite
|
Sign up to set email alerts
|

Protein-tyrosine kinase CAKβ/PYK2 is activated by binding Ca2+/calmodulin to FERM F2 α2 helix and thus forming its dimer

Abstract: CAKbeta (cell adhesion kinase beta)/PYK2 (proline-rich tyrosine kinase 2) is the second protein-tyrosine kinase of the FAK (focal adhesion kinase) subfamily. It is different from FAK in that it is activated following an increase in cytoplasmic free Ca2+. In the present study we have investigated how Ca2+ activates CAKbeta/PYK2. Calmodulin-agarose bound CAKbeta/PYK2, but not FAK, in the presence of CaCl2. An alpha-helix (F2-alpha2) present in the FERM (band four-point-one, ezrin, radixin, moesin homology) F2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
101
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(110 citation statements)
references
References 26 publications
8
101
0
1
Order By: Relevance
“…The signaling intermediates linking G-protein-coupled receptors with calcium and Pyk2 activation have yet to be fully defined. Separate reports implicate calcium/calmodulin and the myosin light chain kinase as key Pyk2 activators (65,66). In addition to Pyk2, focal adhesion kinase (FAK) and paxillin have previously been shown to play roles in epithelial migration (15,67).…”
Section: Discussionmentioning
confidence: 99%
“…The signaling intermediates linking G-protein-coupled receptors with calcium and Pyk2 activation have yet to be fully defined. Separate reports implicate calcium/calmodulin and the myosin light chain kinase as key Pyk2 activators (65,66). In addition to Pyk2, focal adhesion kinase (FAK) and paxillin have previously been shown to play roles in epithelial migration (15,67).…”
Section: Discussionmentioning
confidence: 99%
“…The functional differences between these isoforms are not known. Although the precise mechanism of Pyk2 activation remains unclear, increase in intracellular free Ca 2? can directly or indirectly induce Pyk2 dimerization and transautophosphorylation at Y402 creating a Src-homology-2 binding site that recruits Src family kinases and activates various signaling pathways [1,5,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the focal adhesion kinase (FAK) signalling pathway is important for cell matrix adhesion and cell-extracellular matrix adhesion (73)(74)(75). Following the connection of integrins and matrix, a series of cellular events are triggered and activated, particularly the FAK signal pathway, in the interaction between cells and matrix (76).…”
Section: Tcm Regulates the Adhesion And Motility Of Cancer Cellsmentioning
confidence: 99%